The Influence of China’s Belt and Road Initiative of Economic Crisis in Sri Lanka - Gunawan, Yordan; Napitupulu, Ichwan Rizki Akbar (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
Sri Lanka, as a country in the South Asian region, is bordered by southeastern India and is in the southern Indian Ocean Sea region. This makes Sri Lanka a country with fast trade and maritime traffic, as well as a seaport. Bilateral connections have existed between Sri Lanka and China since the country's inception, and have been enhanced by financial and other aid supplied to the Sri Lankan government throughout the civil war against the separatist organization Liberation Tigers of Tamil Eelam (LTTE). Negotiations between Sri Lanka and China ended in 2017 with a deal for a Chinese-owned business, China Merchant Port Holdings Company Limited, to acquire almost 85% of Hambantota Port shares for 99 years. Because developed countries clearly have a more dominant role in the process of economic globalization, The research method used is normative law research with a case approach. The results show Sri Lanka's dependence on foreign investment to drive a country's economic growth. Therefore, this study aims to determine the legal arrangements governing the effects of the Belt and Road on the economic crisis in Sri Lanka from the perspective of international law and to determine the positive and negative impacts on the planned project.